Process and Product Innovation in a Vertically Differentiated Monopoly - Luca Lambertini; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We analyse product and process innovations in a monopoly model with vertical differentiation. The incentive towards both kinds of innovation is always larger under social planning than under monopoly. Therefore, the comparison between the two regimes` welfare performance should account for the possibility that the planner and the monopolist adopt different technologies and supply different product ranges.
Keywords: 330